KESENIAN MUSIK BAMBU DI DESA LEMOH TIMUR KECAMATAN TOMBARIRI TIMUR - Langi, Theovani (HOLISTIK, Journal Of Social and Culture, 2015)
The people residing in the tribe nation minahasa having a kind of musical known as bamboo music. Bamboo is called music because all a musical instrument used made of bamboo. All regions which are found in minahasa is entirely know music bamboo. Nevertheless, making the music instruments not could be found all over Minahasa. The manufacture of a musical instrument bamboo this is just could be found in several regions have and one of them in the Lemoh village Tombariri Timur sub-district. Music bamboo is one form of culture which was on the community in the Lemoh Timur village which still survives until now. Communities consider, bamboo music as a tool to channel the emotion good happy and sad, reconcile the heart, deprive tired after working as well as giving spirit emotional, and as the identity of the Lemoh Timur village community. In playing a musical instrument is moderately hard because it should to conduct training, and lack of motivation of parents due to the several people the people residing in Lemoh Timur village, consider in music bamboo not to give additional economic in the family and the lack of motivation from the government to develop music bamboo in society, and these that make bamboo musical performer are steadily declining.Keywords: music, bomboo, community